Analysis of Basic Shooting Techniques in the Game Futsal Club Smansa Cosmo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The purpose of the study was how big the skill level of basic shooting techniques in the futsal game of the high school Cosmo club. The type of research in this study is a type of descriptive research with quantitative data analysis. The research site is Grand Futsal on Radda road, Belopa District, Luwu Regency. The research will be conducted in February 2023. The population is all high school Cosmo futsal athletes totaling 20 people. The sampling technique is saturated sampling, where all members of the population will be used as samples in the study. The research instrument is a skill test of basic shooting techniques in futsal games. The research data will be analyzed using descriptive percentages with the help of SPSS program version 23.00. The results showed that the basic shooting technique skills in the high school Cosmo club futsal game were in the medium category of 65%. The results showed that the basic shooting technique skills in the high school Cosmo club futsal game were in the medium category of 65%. The conclusion is that futsal extracurricular activities at high school Cosmo have not received strong attention from students to actively participate in futsal extracurricular activities.